Actitud de maestras y maestros hacia el trabajo cooperativo en el aprendizaje de la matemática - Meza Cascante, Luis Gerardo (2010)
This article reports the most important results of the research project “Attitudes of teachers to work cooperatively in the learning of mathematics”, developed in the School of Mathematics at the Technological Institute of Costa Rica under the code 5402-1440-2201. There is a measurement, description and interpretation of the attitude of teachers to work cooperatively in the learning of mathematics, as a result of an exposure to a workshop in which a working cooperatively strategy for learning mathematics was used. The research involved both qualitative and quantitative techniques.